2009
DOI: 10.1103/physrevlett.102.204301
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Luminescence near the Collapse of Laser-Induced Bubbles in Alkali-Salt Solutions

Abstract: A precursor luminescence pulse consisting of atomic line emission is observed as much as 150 nanoseconds prior to the collapse point of laser-created bubbles in alkali-metal solutions. The timing of the emission from neutral Na, Li, and K atoms is strongly dependent on the salt concentration, which appears to result from resonant radiation trapping by the alkali atoms in the bubble. The alkali emission ends at the onset of the blackbody luminescence pulse at the bubble collapse point, and the duration of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…I p depends on the laser wavelength. For example, I p of water is ∼10 13 W/cm 2 for a focused 1064 nm laser [63]; while for a focused 248 nm laser, I p of water is just ∼2 × 10 9 W/cm 2 [64]. The expansion of plasma associated with the breakdown pushes the surrounding liquid, resulting in a cavitation bubble.…”
Section: Laser-induced Bubblesmentioning
confidence: 98%
See 1 more Smart Citation
“…I p depends on the laser wavelength. For example, I p of water is ∼10 13 W/cm 2 for a focused 1064 nm laser [63]; while for a focused 248 nm laser, I p of water is just ∼2 × 10 9 W/cm 2 [64]. The expansion of plasma associated with the breakdown pushes the surrounding liquid, resulting in a cavitation bubble.…”
Section: Laser-induced Bubblesmentioning
confidence: 98%
“…However, pulsed laser focusing in liquid could still induce bubbles by optical breakdown of the liquid when the irradiance is above a threshold I p [62,63]. I p depends on the laser wavelength.…”
Section: Laser-induced Bubblesmentioning
confidence: 99%
“…From the viewpoint of our model the only origin of parent peaks is "lowdensity" emission with the value of about 1 Amg [13]. Recently [12], it was experimentally demonstrated that Na emission can occur in "low-density" phase far from the point of full collapse. Using the model the lower and the upper values of density, when alkali-metal broad-band emission occurs, were estimated ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the line shape can keep the information about the conditions during the time when the emission occurs. Recently it was shown that metal emission occupies a rather long period of time during collapse phase [12]. So we assume that complex profile of metal line forms due to superposition of the spectra generated at different densities of a perturbing medium.…”
Section: Resultsmentioning
confidence: 99%
“…From the viewpoint of our model the only origin of parent peaks is "low density" emission with the value of about 1 Amg [3]. Recently [11], it was experimentally demonstrated that the emission of Na (585-595 nm) in a bubble formed by laser flashing begins several dozen nanoseconds prior to and passes through the maximum before the continuum emission flash (250-450 nm), which is by two order of magnitude shorter. Thus, Na emission can occur in "low density" phase far from the point of full collapse.…”
Section: Resultsmentioning
confidence: 98%